Effect of Pasteurella multocida toxin on vero cell culture - SUNDER, JAI; KUMAR, A A (The Indian Journal of Animal Sciences, 2013)
The effect of Pasteurella multocida toxin (PMT) produced by a toxigenic strain of serotype A: 12 (goat strain) on vero cell monolayer was studied. The cytopathic effect was observed after 7 days of incubation at 37Â°C under 5% carbondioxide tension. The minimum cytopathic dose of tile toxin was 5.8 ug of the crude toxin. The study suggests that the cell culture (vero cells) assay can be adopted for detection and quuntitation of toxin from toxigeniC strams of P. multocida.